Happy together A study on the emotional and sexual satisfaction among selected married couples and live-in partners in Brgy. San Joaquin, Palo, Leyte. - Adamos, Joy Camille E., et al; Arante, Maria Clarissa A.; Malijan, Ma. Flor Anne L. (Joy Camille E. Adamos, Maria Clarisa A. Arante [and] Ma. Flor-Anne L. Malijan, 2010)
This study was conducted with the aim of exploring the nature of married and live-in relationships. The researchers investigated on the level of satisfaction and gender difference among married couples and live-in partners in San Joaquin Palo, Leyte. A 35-item questionnaire was utilized which consists of the factors of a satisfying relationship namely: love, sex, communication, intimacy and personal growth in the first phase of the study. The satisfaction level was tested using the t-test method. Using the mean as the statistical tool for comparing satisfaction, married couples are more satisfied than live-in partners with the mean of 140.2 and 137.5 respectively. On the other hand, there is no significant difference in the level of satisfaction between married couples and live-in partners at alpha =.05. With the same alpha level, men are relatively satisfied compared to women for both married and live-in participants. In the second phase of the study, the researchers conducted an interview to assess the factors that lead to satisfaction, the respondents reported that indeed love, sex, communication, intimacy and personal growth all intertwine in forming a satisfying relationship along with other factors such as the financial status of the couples and the existence of children. Since this study limits only with 10 married couples and 10 live-in partners, it is highly recommended to involve more respondents and explore other factors that may affect to relationship satisfaction.